Challenges to Academic Freedom - Hermanowicz, Joseph C. (Book collections on Project MUSE., 2021)
"The book consists of chapters of multidisciplinary work that informs a social analysis of academic freedom. It examines the current conditions, as well as recent developments, in the status of academic freedom in the United States"--